2020
DOI: 10.1097/aln.0000000000003076
|View full text |Cite
|
Sign up to set email alerts
|

Pain Response to Open Label Placebo in Induced Acute Pain in Healthy Adult Males

Abstract: Background Open label placebos with patient education are effective in reducing chronic pain, and recent studies on their effect on pain have established interest in this field. Nevertheless, data on their effect on acute pain are scarce, and on hyperalgesia and allodynia, absent. This study assessed the effect of open label placebos on acute pain in healthy adult males and the influence of placebo education. Methods Thirty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…Evidence on OLP effects in acute pain on the other hand is limited, yet promising: Findings of two studies investigating the potential of Conditioned OLP (COLP) to reduce pain intensity and opioid dose in patients with spinal cord injury/polytrauma (30) and following spine surgery (31) suggest that COLP might also be effective in acute pain by showing reductions of opioid doses compared to Treatment As Usual (TAU). These results are supported by the findings of several experimental OLP analgesia studies in healthy populations (7,8,(32)(33)(34). However, there is lack of investigations of unconditioned OLP in acute pain.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Evidence on OLP effects in acute pain on the other hand is limited, yet promising: Findings of two studies investigating the potential of Conditioned OLP (COLP) to reduce pain intensity and opioid dose in patients with spinal cord injury/polytrauma (30) and following spine surgery (31) suggest that COLP might also be effective in acute pain by showing reductions of opioid doses compared to Treatment As Usual (TAU). These results are supported by the findings of several experimental OLP analgesia studies in healthy populations (7,8,(32)(33)(34). However, there is lack of investigations of unconditioned OLP in acute pain.…”
Section: Introductionsupporting
confidence: 62%
“…On the other hand, there have also been investigations showing no additional improvement when a treatment rationale was delivered alongside placebo administration: For example, allergic symptoms were similarly reduced even when pills were given without further explanation (19). In line, our recent study on OLP analgesia in healthy male adults (32) showed a comparable effect on pain reduction in both a short education group as well as in a detailed education group. This result is of great importance, because the possibility of providing OLPs with a short education makes them feasible in clinical practice.…”
Section: Treatment Rationalementioning
confidence: 75%
See 1 more Smart Citation
“…Our finding may add more support to accumulating evidence toward potential benefits of placebo and sham treatments with complexity in research and clinical contexts/settings. 57,58…”
Section: Discussionmentioning
confidence: 99%
“…Our finding may add more support to accumulating evidence toward potential benefits of placebo and sham treatments with complexity in research and clinical contexts/settings. 57,58 Second, our study conveys some methodologic strengths: back pain is an ideal medical condition to study our aims because multiple treatment modalities are available, which made a comparative review possible. Third, we used standardized and validated metrics for quantifying the blinding (blinding index) and treatment effects (effect sizes).…”
Section: Discussionmentioning
confidence: 99%